PERBEDAAN PENGARUH METODE PEMBELAJARAN DAN KOORDINASI MATA – TANGAN TERHADAP PENINGKATAN KETEPATAN PUKULAN FOREHAND DRIVE PADA PERMAINAN TENIS MEJA - Munandar, Wahyu (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2015)
The research aims to find out: 1) The effect difference between the learning Massed and Practice method on the improvement of forehand drive placement in the table tenis. 2) The Difference improvement of forehand drive between player owning eye - hand coordination low and high in the table tenis 3) The effect interaction between Practice method and eye - hand coordination on the improvement of Forehand Drive placement.The research was conducted using an experimental method with a 2x2 factorial design. The research was taken place in sport faculty of Makassar state university. The sample of research was 40 persons coming from the number of population of 60 persons. The sampling technique employed was purposive random sampling. The variables of research include independent variables: manipulative involving (massed and distributed practice) and attributive variable involving higher and lower eye hand coordination, and dependent variable: improvement of forehand drive placement in the table tenis. Techniques of collecting data employed were test and measurement, eye hand coordination test with “lempar tangkap bola tennis test” and forehand drive placement test with “forehand drive placement test”. Technique of analyzing data used was variance analysis (ANAVA) 2x2 at significance level α = 0,05. Based on the result of research, it can be concluded that: 1) There is a significant effect of learning method massed and distributed practice on the improvement of forehand drive placement in the table tenis. It can be seen from the Fstat = 4.10 > Ftable = 4.08. 2) There is a significant result the improvement of forehand drive placement between players with higher and lower eye hand coordination in the table tenis. It can be seen from Fstat = 6.02 > Ftable = 4.08. 3) There is no significant the effect interaction between learning method and eye hand coordination on the improvement of forehand drive placement in the table tenis. Because of Fstat = 0.05 < Ftable = 4.08.